Program Penghijauan di Desa Mallongi-Longi Melalui Program SIGMA (Systematic Greening Management) - Irwan; Side, Syafruddin; Pratama, Muh. Isbar; Mallolongeng, Fitrah; Zahra, Nora Auliya; Hidayat, Syarif (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Mallong- Longi Village, Lanrisang District, Pinrang Regency, South Sulawesi Province is the location for the implementation of the 2022 UNM KKNT team from the 2019 Mathematics study program. The people of Mallongi-Longi Village mostly make a living for farmers/planters. The problem that is still faced by the village community is that there has not been a healthy and beautiful environment in the home environment and its surroundings. The solution to this problem is to green through the SIGMA program. Greening management program to create a healthy and beautiful environment through planting hundreds of tree seedlings in accordance with the reforestation program and various other types of plants in the village environment. Furthermore, from the solution above, a work program in the form of SIGMA Day was formed, then the activity method used by the work program is to carry out a greening program in accordance with the systematics of the SIGMA work program. The results obtained during the implementation of the work program were the planting and distribution of tree seedlings in residents' homes and the surrounding environment of Mallongi-Longi Village.